Pharmacokinetics and tissue distribution of tenofovir, emtricitabine and dolutegravir in mice. (12th January 2022) - Labarthe, Laura; Gelé, Thibaut; Gouget, Hélène; Benzemrane, Mariam-Sarah; Le Calvez, Pauline; Legrand, Nicolas; Lambotte, Olivier; Le Grand, Roger; Bourgeois, Christine; Barrail-Tran, Aurélie
Abstract: Background: Studies of antiretroviral drug (ARV) tissue distribution in preclinical models, such as mice, are key to understanding viral persistence. Objectives: To determine the plasma and tissue pharmacokinetics and tissue distributions of tenofovir, emtricitabine and dolutegravir in mice. Methods: ARVs were simultaneously administered to two different strains, and their levels in plasma and tissue samples were determined by a validated LC-MS/MS method. A non-compartmental analysis was performed to estimate the main pharmacokinetic parameters. A tissue penetration factor (TPF) was calculated as the ratio of the concentration in the tissue concerned to that in plasma. Results: ARV plasma pharmacokinetic parameters in both strains were similar to those estimated in the clinical context. Tissue concentrations were highest in the digestive tract, followed by the liver and kidneys, lymphatic system, pancreas, adipose tissue and lungs. Tissue concentrations were lowest in the brain. Triple therapy could not be considered effective in any of the tissues considered. The TPF values obtained showed that tenofovir diffused widely, especially in the digestive tract, liver and kidneys. Emtricitabine had a TPF above 100% in two-thirds of the tissues. Dolutegravir was poorly distributed to all tissues. Conclusions: Drug specificity was observed, with higher levels of exposure to tenofovir than to emtricitabine or dolutegravir. Tissue specificity was also observed, with strong penetration of the digestive tract and weak penetration of the brain. These data have important implications for future preclinical and clinical studies for developing new HIV therapies with the goal of an HIV cure.